2012
DOI: 10.1128/jb.00510-12
|View full text |Cite
|
Sign up to set email alerts
|

Hfq Influences Multiple Transport Systems and Virulence in the Plant Pathogen Agrobacterium tumefaciens

Abstract: The Hfq protein mediates gene regulation by small RNAs (sRNAs) in about 50% of all bacteria. Depending on the species, phenotypic defects of an hfq mutant range from mild to severe. Here, we document that the purified Hfq protein of the plant pathogen and natural genetic engineer Agrobacterium tumefaciens binds to the previously described sRNA AbcR1 and its target mRNA atu2422 , which codes for the substrate binding protein of an ABC trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 76 publications
9
70
0
Order By: Relevance
“…AB902 showed a severe growth defect in LB solid medium (see Fig. S6 in the supplemental material), which is consistent with previous observations (39). Subsequently, we checked the expression of GaaP in minimal medium supplemented with galacturonic acid as the sole carbon source.…”
Section: Residue R169 In the Proposed Binding Pocket Of Gaap Is Critisupporting
confidence: 72%
See 1 more Smart Citation
“…AB902 showed a severe growth defect in LB solid medium (see Fig. S6 in the supplemental material), which is consistent with previous observations (39). Subsequently, we checked the expression of GaaP in minimal medium supplemented with galacturonic acid as the sole carbon source.…”
Section: Residue R169 In the Proposed Binding Pocket Of Gaap Is Critisupporting
confidence: 72%
“…Further, we demonstrated that the expression of the gaaPQM operon is induced by its substrate sugars and is regulated by the repressor GaaR, which can bind to multiple proposed promoter regions near the catabolic and transporter genes. We also showed that the expression of this operon is not regulated by the small-RNA binding protein Hfq, which has been shown to be important in the control of many sugar binding proteins in A. tumefaciens (39,40). Finally, we demonstrated that the expression of this GaaPQM transporter also affected the expression of virulence genes, which further supports and broadens our previous model in which the sugar transporters are indirectly involved in the control of virulence gene expression (15).…”
supporting
confidence: 72%
“…recA was used as an endogenous control for data analysis (45). Data were collected using a StepOne Plus real-time PCR system (Applied Biosystems) and analyzed using the Relative Expression software tool as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
“…Although the contribution of Hfq and Hfq-regulated sRNAs to virulence has been described in detail in bacterial pathogens of animals, the role of Hfq and Hfq-regulated sRNAs in virulence and host colonization has been reported in only one bacterial plant pathogen, Agrobacterium tumefaciens (36). We hypothesized that Hfq and Hfq-regulated sRNAs would regulate the critical components of pathogenesis in E. amylovora, including the T3SS and amylovoran exopolysaccharide biosynthesis.…”
mentioning
confidence: 99%
“…Moreover, the role of Hfq in environmental adaptations and the control of virulence factors have been identified in major pathogenic bacteria (17). The global role of Hfq in bacterial physiology has been further correlated with considerable changes in gene expression and with a great number of Hfq-associated RNAs in several bacterial species (18)(19)(20)(21)(22)(23). This protein generally increases the intracellular half-life of sRNAs and stabilizes the interactions between sRNAs and their target mRNAs, leading to negative or positive modulation of gene expression at the level of translation or RNA stability.…”
mentioning
confidence: 99%